The increase of artropodofauna as an action of defense against pollution - Algieri, Maria Carmela; Stepancich, Daria (Italian journal of engineering geology and environment, 2018)
<span data-sheets-value="{"1":2,"2":"This paper illustrates the importance of biodiversity, in particular of the arthropodofauna, as it guarantees a series of ecosystem services needed to improve the quality of life. The importance of biodiversity has been acknowledged globally since it depends on a wide range of ecological functions defined as “ecosystem services” such as the production of essential goods, the reduction of pollutants, climate regulation and the regulation of waters. In this context, among environmental improvements is included in the increase in biodiversity and restoring natural processes typical of an equilibrium ecosystem by creating shelter\rand supply areas. Specifically, the increase in arthropodofauna can be facilitated by the design and management of structures and natural elements such as bug’s hotels, hedges and rows, which can provide shelter and trophic resources to the various species."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">This paper illustrates the importance of biodiversity, in particular of the arthropodofauna, as it guarantees a series of ecosystem services needed to improve the quality of life. The importance of biodiversity has been acknowledged globally since it depends on a wide range of ecological functions defined as “ecosystem services” such as the production of essential goods, the reduction of pollutants, climate regulation and the regulation of waters. In this context, among environmental improvements is included in the increase in biodiversity and restoring natural processes typical of an equilibrium ecosystem by creating shelter and supply areas. Specifically, the increase in arthropodofauna can be facilitated by the design and management of structures and natural elements such as bug’s hotels, hedges and rows, which can provide shelter and trophic resources to the various species.